ANALISIS KEPENTINGAN DAN KINERJA TERHADAP PRODUK WISATA DI DAGO DREAMPARK LEMBANG KABUPATEN BANDUNG BARAT - Adrika Triyoga, - (2018)
The purpose of this research is to analyze the interests and performance in dago dreampark lembang bandung regency western visitors through a performance on the extent of interest and the products of tourism in west dreampark dago lembang bandung regency. Three indicators of tourist products, attraction, facilities, and accessibility.This study in a descriptive with the quantitative approach that uses the technique simple random sampling .This study involving 100 respondents using a questionnaire as a means of research. To identify the kepentigan and performance of the important tourism used method of performance analysis science that produces a diagram kartesius there are four quadrants with priority scale. The result of this research, express its strongest the level of the performance of from products of tourist destinations in dago dreampark lembang bandung regency the west which already good, but the extent of the interest visitors in caring for the product sights in dago dreampark lembang kabupaten west bandung higher than the percentage of the value of in terms of performance. There have been instances of 3 a quadrant resulting from a method of installations ipa as well as basis for issuing a reference for those handling to be able to consider the condition of the product of tourism in dago dreampark lembang kabupaten west bandung and is feasible to be maintaining our performance from products of tourist attraction although last year who were judged to be by the visitor already good . ;---Tujuan dari penelitian ini adalah untuk menganalisis Kepentingan dan Kinerja di Dago Dreampark Lembang Kabupaten Bandung Barat melalui penilaian Pengunjung terhadap tingkat kepentingan dan tingkat kinerja produk wisata di Dago Dreampark Lembang Kabupaten Bandung Barat. Terdapat tiga indikator produk wisata yaitu, atraksi, fasilitas, dan aksesibilitas. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif yang menggunakan teknik Simple Random Sampling. Penelitian ini melibatkan 100 responden dengan menggunakan kuesioner sebagai alat penelitian. Untuk identifikasi tingkat kepentigan dan kinerja terhadap produk wisata digunakan metode important performance analysis (IPA) yang menghasilkan Diagram Kartesius terdapat empat kuadran dengan skala prioritas. Hasil penelitian ini, menunjukan tingkat kinerja dari produk wisata di Dago Dreampark Lembang Kabupaten Bandung Barat yang sudah baik, namun tingkat kepentingan Pengunjung terhadap produk wisata yang ada di Dago Dreampark Lembang Kabupaten Bandung Barat lebih besar dibandingkan dengan nilai kinerjanya. Terdapat 3 kuadran yang dihasilkan dari metode (IPA) yang menjadi acuan bagi pengelola untuk dapat memperhatikan kondisi produk wisata di Dago Dreampark Lembang Kabupaten Bandung Barat serta dapat mempertahankan kinerja dari produk wisata yang dinilai oleh Pengunjung sudah baik.